IL-13Rα2 uses TMEM219 in chitinase 3-like-1-induced signalling and effector responses - Lee, Chang-Min; He, Chuan Hua; Nour, Adel M.; Zhou, Yang; Ma, Bing; Park, Jin Wook; Kim, Kyung Hee; Cruz, Charles Dela; Sharma, Lokesh; Nasr, Mahmoud L.; Modis, Yorgo; Lee, Chun Geun; et al. (Nature communications, 2016)
Recent studies demonstrated that chitinase 3-like-1 (Chi3l1) binds to and signals via IL-13Rα2. However, the mechanism that IL-13Rα2 uses to mediate the effects of Chi3l1 has not been defined. Here, we demonstrate that the membrane protein, TMEM219, is a binding partner of IL-13Rα2 using yeast two-hybrid, co-immunoprecipitation, co-localization and bimolecular fluorescence complementation assays. Furthermore, fluorescence anisotropy nanodisc assays revealed a direct physical interaction between TMEM219 and IL-13Rα2-Chi3l1 complexes. Null mutations or siRNA silencing of TMEM219 or IL-13Rα2 similarly decreased Chi3l1-stimulated epithelial cell HB-EGF production and macrophage MAPK/Erk and PKB/Akt activation. Null mutations of TMEM219 or IL-13Rα2 also phenocopied one another as regards the ability of Chi3l1 to inhibit oxidant-induced apoptosis and lung injury, promote melanoma metastasis and stimulate TGF-β1. TMEM219 also contributed to the decoy function of IL-13Rα2. These studies demonstrate that TMEM219 plays a critical role in Chi3l1-induced IL-13Rα2 mediated signalling and tissue responses. Chitinase 3-like 1 regulates cell death, inflammation and tissue remodelling via IL-13receptorα2. Here, the authors show that TMEM219 is a IL-13Rα2 co-receptor and modulates oxidant-induced apoptosis and lung injury, melanoma metastasis and TGF-β1 signalling, downstream of Chi3l1-IL-13Rα2.